2007
DOI: 10.1007/s00299-007-0425-5
|View full text |Cite
|
Sign up to set email alerts
|

Cellular redox-status is associated with regulation of frond division in Spirodela polyrrhiza

Abstract: We investigated a possible relationship between the levels of reactive oxygen species (ROS) and the stimulation of frond division of the aquatic plant Spirodela polyrrhiza (duckweed) during a 7-day experimental culture period. In particular, we monitored superoxide concentration using a state-of-the-art cell biosensor. A considerable reduction in ROS and superoxide concentration was observed during the first 2 days of culture, whereas duckweed cultures achieved near exponential growth rates after the second da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…This means that the AgCl electrode system applied is able to measure conductivity alterations of the extracellular microenvironment reflecting the bioelectric profiling of cell responses to various treatments [60]. It has been previously demonstrated that by using this superoxide biosensor system it is possible to rapidly measure superoxide concentrations as low as 1 pM [43] and also to correlate the biosensor response with currently available conventional methods for superoxide determination [43,50,61].…”
Section: Discussionmentioning
confidence: 99%
“…This means that the AgCl electrode system applied is able to measure conductivity alterations of the extracellular microenvironment reflecting the bioelectric profiling of cell responses to various treatments [60]. It has been previously demonstrated that by using this superoxide biosensor system it is possible to rapidly measure superoxide concentrations as low as 1 pM [43] and also to correlate the biosensor response with currently available conventional methods for superoxide determination [43,50,61].…”
Section: Discussionmentioning
confidence: 99%
“…Membrane‐engineered cells have been developed and used as biorecognition elements in a plethora of applications, including the detection of superoxide (Moschopoulou and Kintzios, ; Moschopoulou et al ., , ), human viruses (Hepatitis B) (Perdikaris et al ., ), plant viruses (Gramberg et al ., ; Moschopoulou et al ., ; Perdikaris et al ., ), organic compounds such as 2,4,6‐trichloroanisole (Varelas et al ., ), aflatoxins (Larou et al ., ), metabolic diseases, prions, foot‐and‐mouth disease virus, and bluetongue virus (Kintzios, ).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the accumulation of oxidized lipids and proteins was increased. It is possible that increased culture growth in liquid media is associated with lower levels of ROS accumulation in proliferating cells, as demonstrated for the concentration of superoxide anion in Echinacea angustifolia (Ali et al 2006) and Spirodela polyrrhiza (Moschopoulou et al 2007), but also lower levels of antioxidants, as observed for ascorbate in cucumber (Cucumis sativus) (Konstas and Kintzios 2003). In spite of the decreased free radical concentrations, increased oxidization of lipids and proteins may have been associated with the concomitant reduction of the investigated antioxidant defence systems of coffee cultures.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, ROS-induced signals for embryonic development could have been mediated via oxidatively modified proteins (protein carbonyls), since their accumulation was positively correlated with the induction of somatic embryogenesis. In a quite recent report, Moschopoulou et al (2007) investigated the possible signaling function of ROS for the stimulation of frond division of duckweeds (Spirodela polyrrhiza). A division-promoting effect was attributed to the observed reduction of free radicals and the associated avoidance of cell apoptotic pathways in cultured plants.…”
Section: Discussionmentioning
confidence: 99%